SIMILARITIES AND DIFFERENCES OF TENSE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - ZIYODULLAYEVA MARJONA , (TADQIQOTLAR.UZ, 2024)
ABSTRACT This paper gives a comparative analysis of the worrying structures in English and Uzbek, two linguistically far away languages. While each languages have complicated annoying structures, there are excellent similarities and variations in how they specific temporal relationships. The English hectic gadget is characterised via a clear difference between past, present, and future, with additional nuances conveyed thru the use of ideal and progressive aspects. In contrast, the Uzbek anxious machine is extra aspectual in nature, focusing on distinctions between completed and ongoing actions instead than strict time reference.Key similarities include the presence of past, present, and future tenses, as nicely as the use of auxiliary verbs to assemble complex anxious forms. However, Uzbek lacks the sturdy machine of ideal and continuous components located in English. Additionally, Uzbek well-knownshows a greater difficult gadget of evidentiality, with distinct verb varieties used to indicate direct journey versus pronounced information.The analysis explores how these structural variations form the expression of temporality, modality, and evidentiality in each language. The findings have implications for language learning, translation, and our broader perception of cross-linguistic version in grammatical systems.